European Yearbook of International Economic Law 2011
XVIII, 522 p.
Keywords: Part one of Vol. 2 (2011) of the European Yearbook of International Economic Law adresses two major topics of current academic debate and public interest: firstly, it focuses on the State and the Global Economy, secondly, on Climate Change and International Economic Law. Part two contains treatises of recent regional integration developments taking place in the major regions of the world. Part three covers the legal and political developments in the major international organizations and fora dealing with international economic policy making. Part four contains book reviews of recent works in the field of International Economic Law.